The complete chloroplast genome of Celtis julianae (Ulmaceae) - Wang, Xudong (Mitochondrial DNA B Resour, 2021)
Celtis julianae C.K. Schneid. is a large deciduous tree of Ulmaceae. In this study, the chloroplast genome sequence of C. julianae was 159,064 bp in length, consisting of a large single-copy (LSC) region with 86,139 bp, a small single-copy (SSC) region with 19,137 bp, and two inverted repeat regions (IRs) with 26,894 bp. The GC content in the chloroplast genome of C. julianae was 36.3%. The chloroplast genome of C. julianae contained 127 genes, including 86 protein-coding genes, 37 tRNA genes, and four rRNA genes. Phylogenetic tree showed that C. julianae was clustered with C. tetrandra.